THE CONSTITUTION OF THE REPUBLIC OF UZBEKISTAN IS A GUARANTEE OF PROGRESS AND DEVELOPMENT (American Journal of Interdisciplinary Research and Development, 2024)
In this article has been analyzed the Constitution of the Republic of Uzbekistan and by this law country become sovereign, democratic, legal and social state by the helping scientific literatures and media sources as well.